Conflict Management Resolution and Peace - Building: A Handbook - Inyom, Nathan N. (Zobak Nig. Ltd, 2013)
This book is an elaborate guide on the principles and practice of peace building conflict management and resolution. It contains basic theories and practical examples of the resolution of various types of crises especially in the contemporary Nigerian context...
Keywords: Non-Fiction / Conflict Management / Conflict Resolution